KKN DESA SALUT UNRAM 2023 : STRATEGI MITIGASI BENCANA GEMPA BUMI DAN KEKERINGAN DI DESA SALUT KECAMATAN KAYANGAN KABUPATEN LOMBOK UTARA - Fricillya, Willa Amanda; Rosyadi , Muhammad Arwan; Abdan, Khaled; Nufus, Husniatun; Fitrah, Jannatul; Kertalam, Lalu Rizki Aji; Mirnawati; Putri, Rizka Amelia; Janna, Ilza Lail Fatul; Sami, Maulana Ananda (Universitas Mataram, 2024)
Salut Village is a village located in Kayangan District, North Lombok Regency, West Nusa Tenggara Province. Salut Village faces various problems, one of which is natural disasters. This village is indicated as an area prone to earthquakes and drought. So it is necessary to optimize mitigation activities in the Salut village area. Based on Law Number 24 of 2007 concerning Disaster Management and the Tridharma of Higher Education which has a strategic role in disaster management, especially related to learning, research and community service. This service aims to find out disaster mitigation strategies that can be implemented in Salut Village. The method used is to carry out a quantitative descriptive approach and inductive data analysis through access to data obtained from interviews, observations and documentation. The results of this service activity include outreach on disaster mitigation in collaboration with BPBD to provide information related to disaster risk reduction efforts and impacts caused by disasters, both natural disasters and man-made disasters. Apart from that, planting trees in areas prone to drought and making evacuation route signs as signs to protect or save yourself when something happens.